Creating A Linear Regression Curve For Loi (Loss Of Ignition) Testing PT Semen Tonasa Hotmeal Using X-Ray - Lengke, Grenatha; Cam, Muhammad Apris; SarungAllo, Rosalia Sira (Jurnal Multidisiplin Indonesia, 2023)
PT Semen Tonasa, especially in the Quality Control unit, still has samples that are tested manually, including the Blaine test, residue test, kiln feed and cement, moisture, and LOI (Loss Of Ignition) so it takes a long time for sample preparation to sample testing. The time to test each sample takes an average of 60 minutes. One type of test that takes a long time is LOI (Loss Of Ingnation) analysis. This test is a test used in inorganic chemical analysis, especially in mineral analysis, by subjecting the sample to a certain temperature. The general objective of this research is to determine the Hotmeal LOI analysis curve for calculating LOI on Hotmeal 05 and 10 and determine the sample preparation steps that will be used in creating a linear regression equation. Meanwhile, the specific aim of this research is to create a formula that is suitable for calculating LOI (Loss of Remembrance) specifically for hot meals 05 and 10. This research was carried out using direct experimental methods and data processing using Microsoft Excel 2013 software. The research was carried out by taking directly raw materials in the form of clinker lumps and Kiln Feed in the factory area, and then preparation and data processing were carried out. The results of this research are that a linear regression equation is obtained, namely y= 1.1824x-6.9094, then this equation is input into a computer device with the method name, namely Hotmeal_2023, to be used as a reference in working on the Hotmeal Sample more quickly, the time used when using this formula is 5 -10 minutes.